Association between surgical tracheostomy and chronic tracheal stenosis: A retrospective, single-center study - Kuwabara, Yuki; Yamakawa, Kentaro; Okui, Seiko; Miyazaki, Erica; Uezono, Shoichi (Frontiers in Medicine, 2022)
Tracheal stenosis is a major complication of tracheostomy. Accordingly, anesthesiologists tend to select a smaller endotracheal tube (ETT) than usual for patients with a prior tracheostomy history, regardless of the presence or absence of respiratory symptoms. However, it likely comes from our trial and error, not scientific evidence. Therefore, in this study, we retrospectively examined the association between traditional surgical tracheostomy and tracheal stenosis as assessed by transverse computed tomography (CT).